PROBLEMS OF DETERMINATION OF GROUNDWATER BODY AT CROSS-BORDER REGIONS OF UKRAINE ACCORDING TO EU WATER LEGISLATION - Koshliakov, O.; Dyniak, O.; Koshliakova, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article considers the problems with the interconnection between surface water and groundwater in cross-border regions of Ukraine according to EU water legislation. It is also clear that cross-border water systems (including groundwater) should be estimated not only factographically (digital mapping based on geoinformational systems), but must also be ranked by the degree of possible cross-border problems occurrence risks. Also the problem is complicated by the fact that groundwater is a dynamic component of subsoil, water resources and ecosystems (environment), so groundwater management is very complex, multidimensional and multi-purpose, and specific assessing and managing groundwater schemes are developed based on the ultimate goal. When selecting groundwater arrays, existing hydrogeological stratification and specificities of vertical and horizontal water exchange conditions in the area must be taken into account.
Keywords: body of groundwater; cross-border water systems; anthropogenic impact